A revision of the mealybug genus Scaptococcus McKenzie (Hemiptera: Coccomorpha: Pseudococcidae), with descriptions of the adult male and female of Scaptococcus occultans sp. n. from the southwestern United States, and the male of S. milleri McKenzie - Von Ellenrieder, Natalia; Watson, Gillian W. (Zootaxa, 2019)
The adult female and male of Scaptococcus occultans sp. n. (Hemiptera: Coccomorpha: Pseudococcidae), a new mealybug species from the southwestern United States, are described and illustrated, as well as the male of S. milleri McKenzie. Females of the new species can be recognized by their unmodified prothoracic legs, anal ring with two rows of cellular pores, and presence of a circulus; the adult female is further characterized by the presence of bands across the thoracic and abdominal segments containing numerous dorsal modified oral collar tubular ducts (with the inner half of the outer duct sclerotized), quinquelocular pores and multilocular pores. The adult male of the new species differs from that of S. milleri by having unmodified prothoracic femora, small spine-like prothoracic claw denticles, fewer dorsal and ventral setae on abdominal segments II–V, and no sclerotized abdominal tergites laterally on the abdomen. The generic description of Scaptococcus is revised to include the new species, and an updated key to the adult females, diagnostic notes for the female nymphal instars, and updated distribution and host data for all the three species are provided.